Peranan Media Berbasis TPACK Terhadap Hasil Belajar Siswa Kelas IV Mi Muhammadiyah Sentono Tahun Ajaran 2023/2024 - Erika Rahmawati; Putri Zudhah Ferryka; Isna Rahmawati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The 21st century is an era of technological advancement in this century technology plays an important role in human life from various aspects including in the world of education. Teachers are required to integrate technology in learning activities. TPACK, which stands for Technological Pedagogical and Content Knowledge, is a new understanding that has become a framework that can be used to analyze educators' knowledge about the use of technology in learning. The problems in this study are (1) how to implement TPACK in learning at MI Muhammadiyah Sentono Klaten (2) teacher obstacles in implementing TPACK. The purpose of this study was to determine the learning outcomes of grade IV students of MI Muhammadiyah Sentono Klaten before and after implementing the TPACK (Technological Pedagogical Content Knowledge) approach, and to determine how much influence it has on the learning outcomes of grade IV students of MI Muhammadiyah Sentono Klaten. This study is a quantitative study with descriptive and comparative methods. The descriptive method is a research method to create a picture of a situation or event, while comparative is a study that uses the technique of comparing one object with another object with interview, observation and documentation techniques.